2022
DOI: 10.3390/s22249725
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-Printed Capacitive Smart Insole for Plantar Pressure Monitoring

Abstract: Gait analysis refers to the systematic study of human locomotion and finds numerous applications in the fields of clinical monitoring, rehabilitation, sports science and robotics. Wearable sensors for real-time gait monitoring have emerged as an attractive alternative to the traditional clinical-based techniques, owing to their low cost and portability. In addition, 3D printing technology has recently drawn increased interest for the manufacturing of sensors, considering the advantages of diminished fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…This is supported by previous studies, which have found that lattice structures display a power law relationship dependent on the structure relative density and compressive properties [47]- [49]. The three designs exhibited hysteresis during the loading and unloading cycle, a behaviour observed in TPU auxetic lattice structures fabricated using SLS [50] and in fused filament fabricated manufactured capacitive pressure sensors for plantar monitoring [51]. The compressive velocity of 4 and 30 mm • min −1 produced similar mean trajectories (Fig.…”
Section: Iiiresults and Discussionsupporting
confidence: 86%
“…This is supported by previous studies, which have found that lattice structures display a power law relationship dependent on the structure relative density and compressive properties [47]- [49]. The three designs exhibited hysteresis during the loading and unloading cycle, a behaviour observed in TPU auxetic lattice structures fabricated using SLS [50] and in fused filament fabricated manufactured capacitive pressure sensors for plantar monitoring [51]. The compressive velocity of 4 and 30 mm • min −1 produced similar mean trajectories (Fig.…”
Section: Iiiresults and Discussionsupporting
confidence: 86%
“…Precise, reliable, and meaningful gait measurements in both high and low-pressure regions, essential for detecting human movement, require soft and flexible sensors with high sensitivity and linearity [13,14]. These characteristics ensure the sensor's efficacy in accurately capturing the nuances of human motion, offering valuable insights applicable to both clinical and research settings.…”
Section: Sensor Performance and Characteristicsmentioning
confidence: 99%
“…Dynamic forces were also applied, as depicted in Figure 4B, revealing an increase in capacitance with increasing pressure. To verify the stability of capacitance under consistent force, a pressure of 100 kPa was applied to the sensor using a force gauge, and the capacitance was repeatedly measured, as shown in Figure 4C [11][12][13]. Figure 4D shows the variation in relative capacitive change for loading and unloading, which indicates low hysteresis.…”
Section: High-pressure Performancementioning
confidence: 99%
See 2 more Smart Citations